Indonesia in the South China Sea Dispute: Humble-Hard Power - Verdinand Robertua; Obsatar Sinaga (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2017)
This research discussed the opportunities for Indonesia to act as humble-hard power in South China Sea dispute. Permanent Court of Arbitration’s decision in July 2016 to give South China Sea based on UNCLOS’s regulation has provoked China’s objection. This research question is on how to understand the conception of humble-hard power and the possibility for Indonesia to be humble-hard power in the South China Sea dispute? This article borrowed the concept of humble-hard power from Adam Nieves Johnson. This research shows two findings. First, the recent victory of the Philippines’ case in the Permanent Court of Arbitration (PCA) should be opportunities for Indonesia to play his role as humble-hard power. Secondly, following the announcement of the ruling, there were already signs that the Chinese government was looking for more detailed the implementation of humble-hard power with Indonesia.